2020
DOI: 10.1103/physrevfluids.5.024603
|View full text |Cite
|
Sign up to set email alerts
|

Flow topology dynamics in a three-dimensional phase space for turbulent Rayleigh-Bénard convection

Abstract: We study the flow topology dynamics in terms of the paramount non-linearities of enstrophy and strain production at hard turbulent regimes of Rayleigh-Bénard convection (RBC). To do so, a data-set of direct numerical simulations for an air turbulent RBC at Rayleigh numbers Ra = {10 8 , 10 10 , 10 11 } is analysed. Considering the bulk dynamics therein, the classical 2D mean Lagrangian evolution of Q G and R G invariants of G ≡ ∇u is extended to 3D by decomposing R G into two parts: the strain production, R S ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Contrary to this, our philosophy is that operator symmetries are critical to the dynamics of turbulence and Rayleigh-Bénard configuration studied in Ref. [3]. Instantaneous temperature field at Ra = 10 10 (left) and instantaneous velocity magnitude at Ra = 10 11 (right) for a span-wise cross section are shown.…”
Section: Introductionmentioning
confidence: 93%
“…Contrary to this, our philosophy is that operator symmetries are critical to the dynamics of turbulence and Rayleigh-Bénard configuration studied in Ref. [3]. Instantaneous temperature field at Ra = 10 10 (left) and instantaneous velocity magnitude at Ra = 10 11 (right) for a span-wise cross section are shown.…”
Section: Introductionmentioning
confidence: 93%
“…The analyzed data corresponds to the bulk region of the air-filled Rayleigh-Bénard configuration at Ra = 10 11 studied in Ref. [10].…”
Section: Nonlinear Sgs Heat Flux Models For Large-eddy Simulationmentioning
confidence: 99%
“…For more details the reader is referred to [9]. Our future research plans include the extension of this analysis to higher Ra and testing a posteriori the new non-linear SGS heat flux models for air-filled RBC at Ra up to 10 11 [10]. Prior to that, we aim to properly discretize tensorial eddy-diffusivity models.…”
Section: Assessment Of Eddy-viscosity Models At Very Low Prandtl Numbersmentioning
confidence: 99%
“…Tsinober 16 postulated that the enstrophy production is large in S4 topology whereas the strain rate production is concentrated in regions of S1 topology. The flow topology distributions in Rayleigh-Bénard convection, where temperature and velocity fields are intrinsically coupled, are yet to be analysed in detail [17][18][19][20] in comparison to the vast body of literature (e.g. Refs.…”
mentioning
confidence: 99%
“…The analyses by Dabbagh et al [17][18][19] revealed the existence of the teardrop shape in the bulk region away from the walls in Rayleigh-Bénard convection but the small scale structures in the vicinity of the hot and cold walls have not been discussed there in terms of Q and R. Xi et al 20 reported a transition of flow topologies from a quadruple structure to a dipole structure based on Rayleigh number in turbulent Rayleigh-Bénard convection, which has implications on the Nusselt number (or heat transfer rate). A recent analysis revealed that large-scale circulation in Rayleigh-Bénard convection is affected by Prandtl number 21 .…”
mentioning
confidence: 99%